Financial Health and Sexual Reproductive Health For Premarital Couples at Javanese Christian Church - Yusuf Rombe M. Allo; Abitmer Gultom; Melinda Malau; Delvia Sari Lim (IKRA-ITH ABDIMAS, 2025)
This Community Service activity aims to increase community understanding, especiallyamong premarital teenage and adult couples, about the importance of sexual reproductiveeducation and financial management for premarital couples at the Javanese ChristianChurch Jatiluhur Congregation, Jakasampurna, Bekasi, West Java. The program focuseson delivering accurate and comprehensive information regarding reproductive health,biological and psychological changes, the prevention of sexually transmitted diseases, aswell as the importance of maintaining healthy and responsible sexual behavior, along withgood family financial management, which is a crucial foundation for young couplesplanning to get married. It is essential to discuss financial planning before marriage,including aspects such as budgeting, debt management, shared financial goals, andemergency fund preparation. With a deep understanding of financial management, couplescan build a financially stable home life. Themethods used in this activity include interactivecounseling, discussion, and question-and-answer sessions, to ensure that participants gainapplicable and relevant insights for their daily lives, both in terms of sexual reproductivehealth and good and sustainable financial management. The program showed an increasein participants' understanding of the importance of sexual reproductive education and theability to make informed decisions related to reproductive health and responsible financialmanagement sustainably. It is recommended to expand this kind of program to otherchurches as an effort to support the success of marriage holistically. Community Servicehas been carried out at the Central Javanese Christian Church Building, JatiluhurCongregation, Bekasi, West Java.Keywords: financial, pre-marriage, health, reproduction, sexual.